Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm reading a proof of Nakayama's theorem; it says at a certain step that:

For $M$, a finitely generated module on a ring $R, N$ a submodule, and $I$ an ideal of the ring $R$:

If $M = N + IM$, then $M/N = I(M/N)$.

I am definitely sure that this question might seem stupid, but I still can't convince myself about that implication.

The proof hints at the fact that for $x$ say representing a certain class in $M/N$ there is $x'$ in $M$ such as $x+N = I (x'+N)$, but again, isn't that equivalent to saying that $M=IM$?

Is there an isomorphism between $IM/N$ and $I(M/N)$?

I know that I am confused so I thank you in advance for clarifying this for me.

share|cite|improve this question
up vote 3 down vote accepted

In general $N$ might not be a submodule of $IM$, so "$IM/N$" doesn't make sense.

Also, the statement "$M=IM$" means that for any $m\in M$, there is some $m'\in M$ and $r\in I$ such that $m=rm'$. The statement "$M/N=I(M/N)$" means that for any coset $m+N$, there is some $m'+N \in M/N$ and $r\in I$ such that $m+N=r(m'+N)=rm'+N$, but this does not imply that $m=rm'$ unless $N=0$. Thus, $M/N=I(M/N)$ is not equivalent to $M=IM$.

share|cite|improve this answer

You need $I$ to be contained in the Jacobson radical of R so you can apply Nakayama's lemma. First observe that $M/N$ is a finitely generated $A$-module (because M is), now once showing that $M=N + IM$ implies $M/N = I(M/N)$ (just do it by inclusions) then we can conclude by Nakayama's lemma that $M/N$ is the zero-module, i.e $M=N$.

Now to show $M/N = I(M/N)$ well pick $x \in I(M/N)$ then by _definition, we have:

$x = \sum_{i} a_{i} (m_{i}+ N)$ where the sum is finite and $a_{i} \in $I, $m_{i} \in M$.

By definition of the operations in the quotient module $M/N$ we have:

$x = \sum_{i} a_{i}m_{i} + N = (\sum_{i} a_{i}m_{i}) + N$.

Now $M$ is an $R$-module and $a_{i} \in I \subseteq R$ so that the product $a_{i}m_{i}$ lies in $M$ because $M$ is an $R$-module. Since modules are abelian groups then $(\sum_{i} a_{i}m_{i}) \in M$ so that $x \in M/N$ and we are done. Can you see the other inclusion? (hint: it is immediate)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.